ANTI-ATHEROGENIC ACTIVITY OF ETHYL ACETATE AND ETHANOLIC EXTRACTS OF CAESALPINIA BONDUCELLA LINN.F. ON HIGH-FAT DIET-INDUCED ATHEROSCLEROSIS IN RATS - SHAMMAH, CYRIL JANE; THENMOZHI, ANNADURAI (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The aim is to investigate the anti-atherogenic effect of ethyl acetate (EACB) and ethanolic extracts of Caesalpinia bonducella (ETCB) kernels against high-fat diet (HFD) induced atherosclerosis (AS) in male Wistar rats. Methods: Rats were divided into seven groups of six each. Group I served as normal control, group II received HFD (20.5% of wheat flour, 52.6% of roasted bengal gram, 5% of skimmed milk powder, 4% of refined oil, 4% of casein, 4% starch with salt mixture, 9% of coconut oil, 0.5% of choline mixture and vitamin and 0.4% of cholesterol), group III received HFD+Standard drug atorvastatin (1.2 mg/kg b.w.) and the remaining four groups IV, V, VI, and VII received HFD along with EACB (100 and 200 mg/kg b.wt) and HFD along with ETCB (100 and 200 mg/kg b.wt) respectively for 90 days. Anti-atherogenic activity was assessed by quantifying the concentration of serum total cholesterol (TC), triglyceride (TG), low-density lipoprotein (LDL) cholesterol, high-density lipoprotein cholesterol, very LDL cholesterol, and phospholipids (PL). Tissue levels of TC, TG, and PL were also determined. Lipid peroxidation and enzymatic anti-oxidants were determined in the liver, heart, and aorta tissue. The histopathological analysis of the liver and aorta tissue supported the dose-dependent anti-atherogenic effects of EACB and ETCB. Results: EACB and ETCB significantly (p≤0.05) protected the above-mentioned parameters to fall from the normal levels. Conclusion: These observations suggest that the EACB and ETCB have a dose-dependent anti-atherogenic effect against HFD-induced AS.